2013
DOI: 10.35790/ebm.1.1.2013.4608
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Perdarahan Antepartum Dan Perdarahan Postpartum

Abstract: The most important cause of hemorrhage in pregnancy and parturition are antepartum hemorrhage and postpartum hemorrhage. The purpose of this research is to investigate the characteristics of antepartum hemorrhage and postpartum hemorrhage at Prof DR. R.D Kandou  General Hospital Manado in 2011. This research used a retrospective descriptive through medical records at BLU RSUP Prof dr R.D Kandou Manado in January 2011 to December 2011. From 4155 parturition case in 2011, there were 60 cases (1,44%) of antepartu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…This study showed the same result with two previous studies that found most of the women with PPH is in 37-42 weeks pregnancy. 16,17 This study showed that most of patients with PPH were resulted from vaginal delivery (93.05%). The previous study had the same result with this study.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…This study showed the same result with two previous studies that found most of the women with PPH is in 37-42 weeks pregnancy. 16,17 This study showed that most of patients with PPH were resulted from vaginal delivery (93.05%). The previous study had the same result with this study.…”
Section: Discussionmentioning
confidence: 90%
“…16 Other study by Londok et al showed that postpartum hemorrhage participants ≥35 years old were the highest percentage. 17 This study discovered that multipara patients were dominant, which was 45.84%. Contrary to this study, the previous studies revealed that primiparity is one of risk factors for PPH.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations